Abducted in Alaska - Turner, Darlene L. (Love inspired suspense., 2021)
"Saving a boy who has escaped his captors puts Canadian border patrol officer Hannah Morgan right into the path of a ruthless child-smuggling ring. Now with help from police constable Layke Jackson, she must keep the child safe. But can they rescue the other abducted children and bring down the gang...all while protecting a little boy and keeping themselves alive?"--Back cover.